2002
DOI: 10.1023/a:1023936421448
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Reactive oxygen species (ROS) cause irreversible damage to biological macromolecules, resulting in many diseases. Reduced water (RW) such as hydrogen-rich electrolyzed reduced water and natural reduced waters like Hita Tenryosui water in Japan and Nordenau water in Germany that are known to improve various diseases, could protect a hamster pancreatic beta cell line, HIT-T15 from alloxan-induced cell damage. Alloxan, a diabetogenic compound, is used to induce type 1 diabetes mellitus in animals. Its diabetogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 28 publications
6
45
0
Order By: Relevance
“…Thus, the results confirmed a previous report. 25) The present results from two different assays capable of measuring endogenous and exogenous H 2 O 2 levels clearly demonstrated that ERW has the potential to reduce and/or scavenge H 2 O 2 .…”
Section: Preparation Of Electrolyzed Reduced Water (Erw)supporting
confidence: 54%
See 2 more Smart Citations
“…Thus, the results confirmed a previous report. 25) The present results from two different assays capable of measuring endogenous and exogenous H 2 O 2 levels clearly demonstrated that ERW has the potential to reduce and/or scavenge H 2 O 2 .…”
Section: Preparation Of Electrolyzed Reduced Water (Erw)supporting
confidence: 54%
“…18,31) ERW has been shown to effectively scavenge intracellular ROS in HIT-T15 cells (a hamster pancreatic cell line). 25) These data together suggest that ERW might regulate VEGF expression by way of ROS. To test this idea and to ascertain if the ROS scavenging activity of ERW is applicable to other cell types, we began by examining the scavenging effect of ERW in A549 cells.…”
Section: Preparation Of Electrolyzed Reduced Water (Erw)mentioning
confidence: 90%
See 1 more Smart Citation
“…W. but not by other natural mineral waters (Li et al 2002). We monitored redox state using a combination of ROS sensitive probe, DCFH-DA, and a con-focal laser microscope or a flow cytometer.…”
Section: Discussionmentioning
confidence: 96%
“…Some natural mineral waters such as Nordenau water found in Germany in 1992 and Hita water (Hita Tenryousui®) found in Japan in 1997 as well as ERW S. Shirahata et al scavenged ROS and protected pancreatic ß-cells from oxidative stress induced by alloxane (Li et al, 2002). Here, we report redox regulation by reduced waters (RWs) for prevention of type 2 diabetes and clinical trials of type 2 diabetes patients.…”
Section: Introductionmentioning
confidence: 80%